Association of Parental Hypertension With Arterial Stiffness in Nonhypertensive Offspring: The Framingham Heart Study. Issue 3 (September 2016) - Andersson, Charlotte; Quiroz, Rene; Enserro, Danielle; Larson, Martin G.; Hamburg, Naomi M.; Vita, Joseph A.; Levy, Daniel; Benjamin, Emelia J.; Mitchell, Gary F.; Vasan, Ramachandran S.
Abstract : High arterial stiffness seems to be causally involved in the pathogenesis of hypertension. We tested the hypothesis that offspring of parents with hypertension may display higher arterial stiffness before clinically manifest hypertension, given that hypertension is a heritable condition. We compared arterial tonometry measures in a sample of 1564 nonhypertensive Framingham Heart Study third-generation cohort participants (mean age: 38 years; 55% women) whose parents were enrolled in the Framingham Offspring Study. A total of 468, 715, and 381 participants had 0 (referent), 1, and 2 parents with hypertension. Parental hypertension was associated with greater offspring mean arterial pressure (multivariable-adjusted estimate=2.9 mm Hg; 95% confidence interval, 1.9–3.9, and 4.2 mm Hg; 95% confidence interval, 2.9–5.5, for 1 and 2 parents with hypertension, respectively; P <0.001 for both) and with greater forward pressure wave amplitude (1.6 mm Hg; 95% confidence interval, 0.6–2.7, and 1.9 mm Hg; 95% confidence interval, 0.6–3.2, for 1 and 2 parents with hypertension, respectively; P =0.003 for both). Carotid–femoral pulse wave velocity and augmentation index displayed similar dose-dependent relations with parental hypertension in sex-, age-, and height-adjusted models, but associations were attenuated on further adjustment. Offspring with at least 1 parent in the upper quartile of augmentation index and carotid–femoral pulse wave velocity had significantly higher values themselves ( P ⩽0.02). In conclusion, in this community-based sample of young, nonhypertensive adults, we observed greater arterial stiffness in offspring of parents with hypertension. These observations are consistent with higher vascular stiffness at an early stage in the pathogenesis of hypertension. Abstract : Supplemental Digital Content is available in the text.